PENGARUH FAMILIARIZATION FLIGHT TERHADAP PEMAHAMAN COCKPIT PROCEDURE PERSONAL ATC DI PERUM LPPNI CABANG MADYA BALIKPAPAN - Ikhsan Wahyu Vebriyan,; Rini Sadiatmi ,; Moh. Budi Kuntjoro, (Langit Biru: Jurnal Ilmiah Aviasi, 2019)
This study aims to obtain an overview of how much the influence of Familiarization Flight on the Understanding of ATC Cockpit Procedure, using quantitative regression research methods. The study concluded that there is a strong positive relationship where the influence of familiarization flight on the understanding of ATC personnel procedure cockpit is 61% and the rest is determined by other factors not examined by the author. With the results above, to further improve the understanding of the ATC personnel procedure cockpit, it is necessary to carry out optimal familiarization flight and be conducted periodically and also conduct debriefing on the cockpit procedure as a provision of knowledge before implementing familiarization flight.